2022
DOI: 10.1186/s13018-022-03229-8
|View full text |Cite
|
Sign up to set email alerts
|

Aseptic femoral nonunion treated with exchange locked nailing with intramedullary augmentation cancellous bone graft

Abstract: Background Closed reamed locked intramedullary nailing has been the treatment of choice for most of femoral shaft fractures. A high union rate with a low complication rate is generally predictable. For an aseptic femoral shaft nonunion with a prior inserted intramedullary nail, exchange nailing is one of favored surgical techniques for treatment. However, a greatly varied success rate of 72–100% has been reported. To improve the success rate of exchange femur nailing, a modified bone grafting t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 35 publications
0
7
0
Order By: Relevance
“…Due to the insufficient addressing of the biomechanics that may underlie nonunion, implant retention is not expedient [ 17 ]. These principles are basically integrated into the single-stage reamed intramedullary exchange nailing, emphasizing the need to remove the previous osteosynthesis material [ 53 , 54 ] and aim for infection eradication to achieve nonunion healing, in combination with the avoidance of infection recurrence in the sense of chronic osteomyelitis after osseous healing, and, finally, the recovery of a sufficient regaining of function [ 55 ]. Nevertheless, the higher number of additional surgical revisions in case of positive bacterial culture necessary until osseous healing demonstrated in this study—44% of the femoral shaft nonunion with and 18% without proof of bacteria—is in accordance with the current multidisciplinary surgical treatment principles for septic diaphyseal femoral nonunion and could be also demonstrated by other studies analyzing nonunion at different locations, observing a revision rate in case of infected nonunion between 6 to 22% [ 56 ].…”
Section: Discussionmentioning
confidence: 99%
“…Due to the insufficient addressing of the biomechanics that may underlie nonunion, implant retention is not expedient [ 17 ]. These principles are basically integrated into the single-stage reamed intramedullary exchange nailing, emphasizing the need to remove the previous osteosynthesis material [ 53 , 54 ] and aim for infection eradication to achieve nonunion healing, in combination with the avoidance of infection recurrence in the sense of chronic osteomyelitis after osseous healing, and, finally, the recovery of a sufficient regaining of function [ 55 ]. Nevertheless, the higher number of additional surgical revisions in case of positive bacterial culture necessary until osseous healing demonstrated in this study—44% of the femoral shaft nonunion with and 18% without proof of bacteria—is in accordance with the current multidisciplinary surgical treatment principles for septic diaphyseal femoral nonunion and could be also demonstrated by other studies analyzing nonunion at different locations, observing a revision rate in case of infected nonunion between 6 to 22% [ 56 ].…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, intramedullary reaming during exchange nailing has been refined and augmented over time, serving as a valuable debridement tool for septic nonunion and a delivery method for intramedullary lavage and antibiotic therapy [ 98 ]. Clinical research utilizing exchange nailing in conjunction with biologic and regenerative therapies is ongoing and offers promising future paths for the treatment of both aseptic and septic nonunion [ 93 , 98 , 99 ].…”
Section: Corrective Techniques and Advancesmentioning
confidence: 99%
“…Of the 16 studies selected, 14 were retrospective [13][14][15][16][17][18][19][20][21][22][23][24][25][26] and 2 were prospective [27,28]. Overall, data from 632 patients were analyzed in our systematic review (summarized data are reported on Table 1).…”
Section: Demographicsmentioning
confidence: 99%